Неруйнівне виявлення реальних дефектів у полімерних композитах за допомогою ультразвукового контролю - Левченко, Є. В. (ХНУРЕ, 2024)
In this study, the results of modeling ultrasonic non-destructive testing of carbon fiber-reinforced plastics (CFRPs) and glass-fiber reinforced plastics (GFRPs) are presented. Initially, ultrasonic C-scan symulation analysis was applied to detect internal defects in composite materials. Subsequently, composite materials were subjected to simulated processing in the area of defect formation, and the obtained results were used to analyze the process using recurrence methods. The results confirmed that recurrence methods can be successfully used to detect defects formed inside the composite material during processing, based on simulated data.
Keywords: дефект у полімерних композитах; ультразвуковий контроль